Relasi Kuasa Dalam Penganggaran Pilkada Kabupaten Bantul Tahun 2020 - Wisnu Prasetyo Aji (ULIL ALBAB : Jurnal Ilmiah Multidisiplin, 2023)
The budget is one aspect that determines the quality of regional elections (Pilkada). The budget issue that emerged in the 2020 Simultaneous Regional Elections was the existence of power relations in the context of preparing the regional election budget, as stated in the text of the Regional Grant Agreement Text (NPHD). There are 2 (two) factors that cause this problem. First, there is a balance of power between institutions in the context of regional election budgeting. Second, the classic problem faced by Indonesia is the lack of uniformity in judicial management (asynchronization between regulations) which has an impact on the quality of regional election budget management. There are differences of opinion regarding regulations, especially the law that regulates the DPRD's authority to carry out budget functions with the technical regulations of the Minister of Home Affairs regarding regional election budgeting. Using descriptive and qualitative research methods, the author will examine budget issues from the perspective of power relations between institutions and budget management for regional elections. The author uses the theory of power relations and election budget management to develop alternative solutions to this problem.